Rancang Bangun Pengumpan Shuttlecock Otomatis - Andito Ramadhani; Nina Paramytha (Universitas Darul Ulum, 2024)
Badminton is one of the most popular sports in Indonesia. This sport not only improves health, but also develops physical, mental and strategic skills. Badminton is also one of the sports that makes Indonesia proud in the international arena thanks to the success of Indonesian badminton players in various world championships. To create reliable badminton players, a very strict training program and the best training facilities are needed, one of which is a drill training program in badminton that feeds continuously, this exercise is very effective depending on how long the ball feeder feeds. Therefore, an innovation to help a coach in training his students, especially in drill training, is an automatic shuttlecock feeder that can feed automatically with varied feeds and with a certain speed that has been programmed using a microcontroller, previously this automatic shuttlecock feeder tool has been made by Reza Kurniawan and Jaka Kurniawan. Still, in this research, the author added a security system using two sensors: an RFID sensor and an ultrasonic sensor.